Transparency and Efficiency Of Innovative Communication Towards Good Governance in Cash Waqf Among Public Universities According to the Mawez Framework - Nafizal Haris Bin Ismail (Universiti Sains Islam Malaysia, 2025)
Matric: 3232399 (FKP)